Analisis kurva isodosis paparan radiasi pada ruang terapi dengan Linear Accelerator (LINAC) 6MV - Ana Aprilia; Eko Hidayanto; Evi Setiawati; Sanggam Ramantisan (Youngster Physics Journal, 2018)
Radiation exposure in the therapy room with linac 6 MV devices has been conducted at Ken Saras hospital. The purpose of this research was to determine the radiation exposure in the therapy room to provide the information for radiation workers regarding the safe location in therapy room using isodose curve presentation and contour mapping of radiation exposure in the therapy room. The results of radiation exposure measurement were then used to calculate the radiation dose received by patients during therapy as patient information. The method used in this research was the direct measurement of radiation exposure in therapy room using survey meter with 130 cm height from the floor at some point with the addition of each 1 meter, field size is 40 cm x 40 cm, absorbed dose is 50 MU and variations of the gantry position, gantry 00, gantry 900 and gantry 2700.  The result of the measurement then used to create a contour using a software and then analysed to point the safe location through a mathematical calculation. The Values of radiation exposure in field size of 40 cm x 40 cm then converted to the value of radiation exposure in field size of 10 cm x 10 cm on a sample study case patient X by multiplying with the value of the inverse square. The converted value is then calculated into the radiation dose received by patients X during therapy. The results showed that the gantry 00 and gantry 2700 position, the safe location in therapy room for radiation worker is at the position (-5.5; -4) with a dose rate of 7.2 μSv / h and 9.6 μSv /h while at gantry 900  position  there is no safe area for radiation workers in the therapy room. The value of exposure radiation that received by the patient X in this research, that undergo once therapy with 4 times exposure at 4 variation gantry position at dose of 50 MU with  10 cm x 10 cm field size is 1196.9502 μSv or 1.197 mSv. Keywords:  radiation exposure, therapy rooms, isodose curve, safe area, patient radiation dose